The Concept of Quantity in the Linguo-Philosophical Understanding of the Russian-Ukrainian War: Case Study of the Works by Borys Humeniuk (Linguostylistic Studies, 2025)
This article highlights the concept of studying the language of fiction in a linguistic aspect. The language material of Borys Humeniuk’s works presents the linguistic content of numerical designations, which are verbalizers of the concept of quantity. The artistic works of B. Humeniuk make us consider whether the form of expressing the number in the text is significant. It is noted that alphanumeric, numerical, and digital information are social by nature: they appeal to a certain experience of the individual. While the text with the letter expression of the number (with numerals) is homogeneous, the text with numbers and symbols like m, km, and % complicates the content. The meaningful filling of figures and numbers in some cases is symbolic, requiring the reflection of the reader’s socio-historical consciousness, while in others, it only slows down the rhythm and melody, gives the expression a practical, official tonality, actualizes landmark images, analogies. It was concluded that the number in the verbal artistic context brings another dimension of reality, another dimension of accuracy, concreteness, or vice versa, abstractness and generalization. With such a figurative, functional, and stylistic component, a complete artistic context appears as an object of social perception – the reader perceives the verbal image of a person by the sensations and emotions it evokes, by specific physical parameters, and a person in space by stereo-geometric features.
Keywords: linguistics; concept; numeral; the language of poetry; language of prose